Landscape Analysis and Planning: Geographical Perspectives - Luc, M (Springer, 2015)
This book presents recent advances in landscape analysis and landscape planning based on selected studies conducted in different parts of Europe. Included are methodological problems and case studies presented and discussed during scientific sessions organized by the Commission of Landscape Analysis and Landscape Planning of the International Geographical Union (IGU) within the framework of the IGU Regional Conference in Kraków, Poland, August 18-22, 2014.